Pengaruh Keterampilan Kerja Dan Komunikasi Terhadap Kinerja Karyawan Di PT. Hayati Putra Mandiri (HPM) - Diky Maulana Ilhami (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the effect of work skills and communication on employee performance at PT. Hayati Putra Mandiri. The phenomenon within the company shows that employees’ work skills in assembling medical equipment and health building construction remain unstable, and communication between employees and supervisors still faces obstacles. The research method applied is quantitative, using a survey with questionnaires distributed to 35 employees, which represent the entire population of the company. Data were analyzed using multiple linear regression along with validity, reliability, and classical assumption tests through SPSS version 25. The results indicate that work skills and communication simultaneously have a positive and significant effect on employee performance. Partially, work skills significantly affect employee performance, and communication also significantly influences employee performance. Further analysis shows that the F test value was 23.76 with a significance of 0.000, while the R² value was 0.65. The t test results for work skills was 4.12 and communication was 3.89, both significant at p < 0.05.